Case Report: Effect of Targeted Therapy With Carbamazepine in KCNQ2 Neonatal Epilepsy - Dilena, Robertino; Mauri, Eleonora; Di Fonzo, Alessio; Bana, Cristina; Ajmone, Paola Francesca; Rigamonti, Claudia; Catenio, Tamara; Gangi, Silvana; Striano, Pasquale; Fumagalli, Monica (Frontiers in Neurology, 2022)
We present a family case of neonatal-onset KCNQ2-related epilepsy due to a novel intronic mutation. Three members of an Italian family (father and offspring) presented with neonatal-onset asymmetric tonic and clonic seizures with peculiar video-electroencephalography and aEEG features referring to sequential seizures. The father and the first son underwent standard of care treatments in line with current neonatal intensive care unit protocols, with a prolonged hospitalization before reaching full seizure control with carbamazepine. After the experience acquired with her family and the latest advances in the literature, the younger daughter was directly treated with carbamazepine, obtaining rapid seizure control and short hospitalization. They all had normal development. Carbamazepine is rarely administered as a first-line option in neonatal seizures. Recent evidence suggests that neonatal intensive care unit protocols should implement a trial with sodium channel blockers such as carbamazepine as first-option anti-seizure medication and a fast access to genetic testing in neonates with sequential seizures without structural brain injury or acute causes. Moreover, we report and discuss the laboratory studies performed on a novel causative intronic mutation in KCNQ2 (c.1525+5 G>A in IVS13), since pathogenicity may be difficult to prove for intronic variants.